2015
DOI: 10.1017/psrm.2015.58
|View full text |Cite
|
Sign up to set email alerts
|

Dependency Status and Demand for Social Insurance: Evidence from Experiments and Surveys

Abstract: Current thinking on the origins and size of the welfare state often ignores household relations in which people may depend on others for income or have dependents themselves. The influence of "dependency status" on individuals' political preferences is unknown. We report results from a laboratory experiment designed to estimate the effect of dependency on preferences for policies that insure against labor market risk. Results indicate that 1) willingness to vote in favor of a social insurance policy is highly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 68 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…First, scholars have used incentivized experiments specifically to study support for social insurance. Generally, participants earn income by completing a real effort task and subsequently vote on a tax rate to finance a social insurance program (e.g., Barber et al, 2013) or whether social insurance should be provided (Ahlquist et al, 2017). Generally, these experiments have found that participants who are exposed to a higher risk of losing their income are more supportive of social insurance.…”
Section: Program Abuse Cooperation and Risk Sharingmentioning
confidence: 99%
“…First, scholars have used incentivized experiments specifically to study support for social insurance. Generally, participants earn income by completing a real effort task and subsequently vote on a tax rate to finance a social insurance program (e.g., Barber et al, 2013) or whether social insurance should be provided (Ahlquist et al, 2017). Generally, these experiments have found that participants who are exposed to a higher risk of losing their income are more supportive of social insurance.…”
Section: Program Abuse Cooperation and Risk Sharingmentioning
confidence: 99%
“…The Varieties of Capitalism framework has provoked a spate of empirical studies around social insurance and skills. Most of these have focused on evaluating the relationship between workers' skills and survey based measures of support for social insurance and redistribution (Ahlquist, Hamman and Jones, 2017;Cusak, Iversen and Rehm, 2006;Gingrich and Ansell, 2012;Iversen and Rhem, 2022;Nickelsburg and Timmons, 2012;Rehm, 2009Rehm, , 2011Sjöberg, 2008;Timmons and Nickelsburg, 2014). These studies face a series of empirical and conceptual challenges.…”
Section: Introductionmentioning
confidence: 99%
“…300ECU:£1 in the lab and 600ECU:$1 on mTurk.15 On the slider task, see Prowse (2011, 2012). SeeAhlquist, Hamman and Jones (2017) for a recent application of this real effort task in the context of social insurance programs.…”
mentioning
confidence: 99%